Prevalence of Human Immunodeficiency Virus, Hepatitis B, Hepatitis C and Syphilis among Antenatal Patients, Gastroenterology Patients and Blood Donors in Public Hospitals in Lagos - Okunade, Kehinde Sharafadeen; Odeghe, Emuobor; Akinlawon, Damilola O; Oladele, Rita O (The Nigerian postgraduate medical journal, 2025)
Background: Blood-borne infections remain a significant public health challenge globally. Understanding their prevalence and risk factors is crucial for implementing preventive measures. Objective: The objective of the study was to determine the prevalence of blood-borne infections, including human immunodeficiency virus (HIV), hepatitis B virus (HBV), hepatitis C virus (HCV) and syphilis, among patients attending public hospitals in Lagos, Nigeria. Subjects and Methods: This was a cross-sectional study involving 352 participants, recruited from the antenatal, gastroenterology clinics and prospective donors from the blood banks in four general and one tertiary hospital in Lagos, Nigeria. Data were collected on demographic characteristics, risk factors and disease prevalence using structured questionnaires, and laboratory testing was performed using the B21147-01 HIV-HCV-HBsAg-Syphilis Combo Rapid Test. Results: The mean age of participants was 37.2 ± 11.0 years. The majority were female (66.8%) and married (80.7%). The prevalence of HIV, hepatitis B surface antigen (HBsAg) anti-HCV, and syphilis was 24.4%, 23.3%, 2.6% and 0.3%, respectively. There was significantly increased odds of HIV infection among participants with a history of sexually transmitted infections (adjusted odds ratio [AOR] = 2.3, 95% confidence interval [CI] = 1.0-5.1), and those who had skilled occupations (AOR = 4.5, 95% CI = 1.5-13.3). Participants with a family history of either HBV, HCV, chronic liver disease or hepatocellular carcinoma had significantly increased odds of being HBsAg positive (AOR = 7.8, 95% CI = 2.1-29.42). Conclusion: Blood-borne viral infections are highly prevalent among people attending hospitals in Lagos, Nigeria. Enhanced screening, awareness and risk reduction education are recommended to reduce the burden of these infections.